Nursing process applied to a client with breast cancer: a case study based on the theoretical framework of Imogene king - Souto, Cláudia Maria Ramos Medeiros; Garcia, Telma Ribeiro; Coler, Marga Simon (Rev Rene, 2000)
This is a clinical case study in which the authors aim to describe an application of the nursing process to a woman with breast cancer, based on the conceptual framework and Theory of Goal Attainment of Imogene King, in the area of domiciliary care. Taxonomy I of the North American Nursing Diagnosis Association (NANDA) was used as a framework for portrays the client’s responses in regarding to her lived health situation. To implement the nursing process, domiciliary visits were conducted and data were gathered through systematic observation and a semi-structured interview. Five nursing diagnoses were identified for which interventions were planned and implemented. The authors selected two out of these fine diagnoses to be presented in this work – Chronic Pain and Spiritual Distress.